Introducing dental students to reflective practice: a dental educator's reflections. Issue 2 (4th March 2018) - Neville, Patricia
Abstract: There is growing consensus that being reflective and developing reflective practice is an important part of becoming a healthcare professional, adding to and enhancing our everyday professional values, knowledge and skills. For dentists, reflective practice is an essential part of dental training and professional development with dental undergraduate curricula creating and scaffolding opportunities for students to be reflective and develop reflective writing skills. This article describes the introduction of a reflective portfolio to the undergraduate Bachelor of Dental Science (BDS) programme at the University of Bristol. This will be followed by the author sharing some personal reflections, as the faculty member overseeing the assessment of these reflective portfolios, on the first year of this initiative. Lessons learned from the exercise as well as areas for future work and improvement will also be mentioned.